Single-bilayer graphene oxide sheet impacts and underlying potential mechanism assessment in germinating faba bean (Vicia faba L.) - Anjum, Naser A.
This study investigates the impact of different single-bilayer graphene oxide sheet (hereafter 'graphene oxide', GO; size: 0.5-5μm) concentrations (0, 100, 200, 400, 800 and 1600mgL-1) and underlying potential mechanisms in germinating faba bean (Vicia faba L.) seedlings. The study revealed both positive and negative concentration-dependent GO-effects on V. faba. Significant negative impacts of GO concentrations (ordered by magnitude of effect: 1600>200>100mgGOL-1) were indicated by decreases in growth parameters and the activity of H2O2-decomposing enzymes (ascorbate peroxidase, APX; catalase, CAT), and by increases in the levels of electrolyte leakage (EL), H2O2, and lipid and protein oxidation. The positive impacts of 400 and 800mgGOL-1 included significant improvements in V. faba health status indicated by decreased levels of EL, H2O2, and lipid and protein oxidation, and by enhanced H2O2-decomposing APX and CAT activity, and increased proline and seed-relative water content. V. faba seedlings-polypeptide patterns strongly substantiated these GO-concentration effects. Overall, the positive effects of these two GO concentrations (800>400mgL-1) on V. faba seedlings indicate their safe nature and allow to suggest further studies.